Peningkatan Kemampuan Fisik Motorik Halus Anak dengan Menggambar Bebas dari Bentuk Dasar Lingkaran pada Kelompok B TK Pertiwi II Cemeng - Sulasih, Sulasih (Universitas Pendidikan Indonesia Kampus Serang, 2023)
The lack of student interest in free-drawing activities is the background for this research. The research was conducted from January 2021 to June 2021. This study aims to describe how to foster creativity in children by free drawing and find out how to increase children's creativity through free drawing in group B Kindergarten Pertiwi II Cemeng Academic Year 2020/2021. Children's creativity needs to be increased, one way is by drawing freely from the basic shape of a circle and then retelling the image. This research is a classroom action research that is collaborative between researchers, school principals, and accompanying classroom teachers. The subjects in this study were group B students of Pertiwi II Cemeng Kindergarten. Data were collected through observation, field notes, interviews, and documentation. The validity of the data was checked by triangulation. Data were analyzed by descriptive qualitative flow model. The results of this study indicate that there is an increase in children's creativity through free drawing, namely before the action up to the second cycle in a row shows an increase, namely in children who show a creative attitude increases to 83.33%. Then in terms of quantity the number of children who can draw proportionally increases to 50.00%. The indicator for children doing their assignments on time increased to 62.50%, children who finished drawing and coloring neatly increased to 75.00%, children who dared to tell the results of the pictures they had made increased to 62.59%, and children whose fluency in telling the pictures it has made increases to 50.00% at the end of the cycle. This shows the effectiveness of this drawing activity in improving children's fine motor skills. This activity can be an alternative solution for teachers who experience the same problem.